PENGARUH RASIO PROFITABILITAS, RASIO LIKUIDITAS TERHADAP NILAI PERUSAHAAN PADA PT. LIPPO KARAWACI Tbk. - Devi, Novitasari; Rimawan, M. (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2022)
The type of data in this study is secondary data obtained from the official website of idx with the aim of knowing and analyzing the relationship between Return on Equity (ROE) and Quick Ratio (QR) to Company Value at PT. Lippo Karawaci Tbk. The population used in this study is the financial statements at PT. Lippo Karawaci Tbk for 25 years (1996-2020). The sampling technique is purposive sampling with a sample of 10 years from 2011 to 2020. The data analysis technique is in the form of classical assumption test, multiple linear regression test, determination test, and t test and f test. The results of the study found that ROE had no and no significant effect on firm value, and the QR variable had a significant effect on firm value.